Sparkling achievements of UiTM Perak Branch / E. Tavasuria Elangovan - Elangovan, E. Tavasuria (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
This event was launched by the State Islamic Religious Affairs, Islamic Education and Personal Development Committee Chairman; the Honorable Dato' Dr. Mohd Nizar Bin Zakaria. Rector of UiTM Perak Branch, Assoc. Prof. Sr. Dr. Md. Yusof Hamid, strategic partners of UiTM Perak Branch; State Islamic Religious Affairs, Islamic Education and Personal Development committee, Malaysia Department of Information (Perak), BankIslam Seri Iskandar Branch, and Federal Agriculture and Marketing Association (FAMA) Perak, as well as the Executive Management board of UiTM Perak Branch. Assoc. Prof. Sr. Dr. Md. Yusof Hamid mentioned in his welcoming speech that a programme such as 'Bulan Inovasi 2017' promotes the culture of innovation and creativity in our community and provides golden opportunities to UiTM staff to express their incredible talents in the field of research and innovation.